AGENT-BASED MODELING TO INFORM ECOLOGICAL COEXISTENCE OF ONLINE COMMUNITIES: IMPACT OF COMMUNITY SIZE, PARTICIPATION COST, TOPIC BREADTH AND POPULATION INTEREST DISTRIBUTION - HAN LUYANG (2017)
Master's